The role of occupational health care in ambulatory health care in Finland - Tuukka Holster; Lien Nguyen; Unto Häkkinen (University of Oslo, 2022)
In Finland, occupational healthcare (OHC) provides alternative access to curative ambulatory primary healthcare for a large proportion of the employed. Providers of occupational and private healthcare can also refer patients to public secondary healthcare, possibly providing better access to specialized medicine. We investigate the determinants of the use of OHC and associations between the use of OHC and other ambulatory service sectors and distributions of ambulatory healthcare. We find that the probability of using OHC is positively associated with the size of the employing organization and is higher for those with higher incomes but does not vary strongly between patients with different health conditions. Those who use OHC visit public health centres less often, but the negative association is not strong: the use of occupational healthcare seems to be associated with an overall higher use of ambulatory services. The results show that ambulatory healthcare is not allocated according to need in Finland. Those with higher incomes are in better health and use more OHC and private healthcare. Published: Online July 2022